O-016 Radiation exposure during cerebral angiography and neuroembolization in children: analysis of 357 consecutive cases. (4th July 2012) - Lin, N; Manchester, J; Smith, E; Scott, M; Orbach, D
Abstract : Introduction/Purpose: Catheter-based cerebral angiography and embolization are important tools in managing cerebrovascular diseases in the pediatric population. We concurrently present data on the safety of pediatric neurointervention, demonstrating an overall low complication rate associated with such procedures in children, regardless of age group. However, radiation exposure during neurointerventional procedures in the pediatric population is of particular importance and merits dedicated study. Materials and Methods: Records for all pediatric patients who underwent cerebral angiography and/or neuroembolization from 2007 through 2009 were retrospectively reviewed. Radiation skin entry dose data were obtained from fluoroscopic suites equipped with built-in cumulative dose (air kerma) and dose-area-product (DAP) measurement capability. Results: Of the 357 consecutive procedures performed from 2007 through 2009, 214 were diagnostic angiograms and 143 involved embolization. Mean age was 9.5 years (range: 4 days to 18 years), and 193 were female. The interventional procedures included intracranial (77), extracranial (57), and spinal (9) embolizations. The pathology requiring neurointervention included intracranial arteriovenous malformation (AVM, 15), spinal AVM (8), aneurysms (15), Vein of Galen Malformation (VOGM, 19), intracranial arteriovenous fistula (AVF, 21), facial and extracranial AVM (46), tumor (11), stroke (2), and others (6). Overall, the observed cumulative dose and DAP correlated well (r=0.87). The average cumulative skin entry dose for the cohort was 365.9 mGy (range: 21–2707 mGy). Radiation exposure during neurointervention was significantly higher than during diagnostic angiography (566.3 and 191.0 mGy, respectively, p<0.001). Patients with spinal AVM (939.8 mGy), aneurysms (777.5 mGy), and AVF (730.5 mGy) received higher doses of radiation. During the mean follow-up period of 2.1 years, one short-term complication (transient hair loss) related to radiation was noted. Conclusion: Relative to previous reports related to neurointerventions in adults and to complex, non-neuro pediatric interventions, radiation exposure during cerebral angiography and embolization was moderate, and the short-term risk associated with radiation was low. It will be of importance, going forward, to track the long-term effects of radiation exposure related to pediatric neurointerventions in this cohort, requiring conversion of skin entry doses to brain organ dose. Competing interests: None.